KEPUASAN PELANGGAN SEBAGAI PEMEDIASI PENGARUH HARGA, KUALITAS PRODUK DAN LOYALITAS PELANGGAN - Rosvania Jouzanda Kathlya; Eristia Lidia Paramita (Faculty of Economics and Business, Universitas Malikussaleh, 2020)
Environmentally friendly fuels are one of the superior commodity lately, BBM Pertamax is one of them that could reduce air pollution. Therefore this study aims to test the influence between price, product quality, customer satisfaction, and customer loyalty. The data in this study used primary data by distributing questionnaires to 290 respondents who lived in Java Island. Then, the characteristics of respondents, as follow: 1) customer who used BBM Pertamax both two wheels and four wheels, 2) customer who used BBM Pertamax one to five years, and 3) used motor vehicle with 10:1 to 11:1 compression ratio. Data were tested using Structural Equation Modeling (SEM) with the AMOS Graphics application. The results showed that there was an effect of product quality on customer satisfaction and there was an influence between price and product quality on customer loyalty through customer satisfaction as a mediating variable. But there is no effect between price on customer satisfaction and customer loyalty, also product quality on customer loyalty.